2020
DOI: 10.1021/acssuschemeng.0c01122
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor Generation Cascade for α-Ketoglutarate and Fe(II)-Dependent Dioxygenases

Abstract: Fe(II)- and α-ketoglutarate dependent dioxygenases have emerged as important catalysts for the preparation of non-natural amino acids. The stoichiometric supply of the cosubstrate α-ketoglutarate (αKG) is an important cost factor. A combination of the N -succinyl amino acid hydroxylase SadA with an l -glutamate oxidase (LGOX) allowed for coupling in situ production of αKG to stereoselective αKG-dependent dioxygenases in a one-pot/two-step cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition to PCP-bound substrates, occasionally N -acylated substrates are hydroxylated by AAH enzymes en route to free OH-AAs (Figure B). For example, SadA is an AAH from Burkholderia ambifaria AMMD, which acts on numerous N -succinyl- l -AAs (e.g., l -Leu, l -Val, l -Ile, l -Cys, l -Met, l -Ala, l -Phe, l -Asp, l -Glu) with various levels of activity . The desuccinylase LasA then unmasks the α-NH 2 to form 3 R -OH-L-AA products.…”
Section: Discoverymentioning
confidence: 99%
“…In addition to PCP-bound substrates, occasionally N -acylated substrates are hydroxylated by AAH enzymes en route to free OH-AAs (Figure B). For example, SadA is an AAH from Burkholderia ambifaria AMMD, which acts on numerous N -succinyl- l -AAs (e.g., l -Leu, l -Val, l -Ile, l -Cys, l -Met, l -Ala, l -Phe, l -Asp, l -Glu) with various levels of activity . The desuccinylase LasA then unmasks the α-NH 2 to form 3 R -OH-L-AA products.…”
Section: Discoverymentioning
confidence: 99%
“…[122] Kourist et al have developed the SadA system by coupling the Fe/αKG with L-glutamate oxidase (LGOX), for the in situ production of co-substrate αKG from L-glutamate. [123] Zaparucha et al have used a genome-mining approach to identify Fe/αKGs able to perform hydroxyl functionalisation with high regio-and stereoselectivity on basic amino acids L-lysine, L-arginine and L-ornithine. [124,125] Kino et al have studied a novel Fe/αKG from Sulfobacillus thermotolerans Y0017 and shown its ability to catalyse the regio-and stereoselective threo-β-hydroxylation of L-histidine and L-glutamine on a preparative scale.…”
Section: Iron-and α-Ketoglutarate-dependent Oxygenasesmentioning
confidence: 99%
“…coli strain lacking the isocitrate lyase and isocitrate dehydrogenase kinase/phosphatase was designed, channeling the endogenously produced cosubstrate α-ketoglutarate toward the αKGDs. In addition, in a one-pot enzymatic cascade reaction with the αKGD N -succinyl amino acid hydroxylase (SadA) catalyzing the hydroxylation of N -succinyl- l -valine to N -succinyl-β-hydroxy- l -valine, in situ production of αKG from l -glutamic acid was resolved with l -glutamate oxidase . In the absence of these approaches, αKGDs can still be considered cost-effective since the reaction requires cheap and abundant O 2 and αKG, which is less expensive than NAD­(P)­H.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a one-pot enzymatic cascade reaction with the αKGD N-succinyl amino acid hydroxylase (SadA) catalyzing the hydroxylation of N- succinyl-L-valine to N-succinyl-β-hydroxy-L-valine, in situ production of αKG from L-glutamic acid was resolved with L-glutamate oxidase. 26 In the absence of these approaches, αKGDs can still be considered cost-effective since the reaction requires cheap and abundant O 2 and αKG, which is less expensive than NAD(P)H. Furthermore, in contrast to P450s, αKGDs are self-sufficient enzymes and do not require a dedicated reductase partner. 27 As an alternative to enzyme engineering, we have chosen to perform genome mining for novel enzymes.…”
Section: ■ Introductionmentioning
confidence: 99%